FREQUENCY OF HEADACHE WITH STRESS IN ADOLESCENT AND YOUNG ADULTS - Nawaz, Khurram Haq; Khan, Muhammad Naeem; Khan, Muhammad Babar; Wali, Muhammad Waseem; Yous, Muhammad Ali; Ahmad, Imran (Pakistan Armed Forces Medical Journal, 2011)
Objective: Objective of this study was to establish a link between stress as a cause of headache in young adults. Study Design: Cross sectional study Place and Duration of Study: Department of Neurology Military Hospital (MH) Rawalpindi from September 2009 to March 2010. Patients and Methods: Thirty young patients, referred for the complaints of headache to the Neurology Out patient department, were included in this study. A detailed especially designed, pre tested headache questionnaire was devised which was filled for every patient individually included in the study. Results: Twenty One (70%) of the patients in the study group did have the feeling of stress preceding the headache which sometimes persisted during the episode. Nine (30%) did not report any such feeling of stress before or during the episode. Out of the patients reporting stress 71 %( 15) were female patients and 29 %( 6) were males. Conclusion: These key findings suggest that stress and headaches may be related for adolescents and young adults and that this relationship may be reinforced over time. Moreover female patients were far more susceptible to this stressful stimulus as compared to the males.